The role of psychiatrists and tobacco dependence treatment - Amer Nordin, A.S.; Sellman, J.D.; Adamson, S.J. (2014)
Objective: Global tobacco control efforts in both prevention and treatment have advanced to levels never imagined 20 years ago. This review examines the relationship between mental illness and tobacco use, with particular focus on the role of psychiatrists in the treatment of tobacco dependence. Methods: The literature search utilised MEDLINE, Embase and PsychINFO databases using the terms psychiatry, psychiatrist, smoking cessation, tobacco use disorder and tobacco dependence treatment. A manual search of all references from relevant scientific articles obtained was also conducted. Finally, further material sourced included all major guidelines for smoking cessation or tobacco dependence treatment from the United States, United Kingdom, Canada, Australia and New Zealand. Results: Psychiatry has ignored tobacco dependence and its treatment resulting in multiple missed opportunities in improving the health and well-being of smokers with mental illness. Improvement in the training and knowledge of psychiatrists and those in the mental health sector will be the most effective activity to rectify this situation. Conclusion: Psychiatry must recognise tobacco dependence as equally important as the primary mental illness and to treat accordingly. A significant change in the training of future psychiatrists, introducing or implementing smoke free mental health services, changes in the management of caring for the mentally ill, and the introduction of tobacco treatment specialists within the mental health system is needed if psychiatry is serious about confronting this problem.